Just the facts101 Machine learning : a probabilistic perspective - Murphy, Kevin P. (Cram101 Publishing, 2013)
Cram101 Textbook Outline notebooks have been designed so you can get the most out of your class and study time. The outlines consist of all the terms, concepts, places, people organisations and events that you may expect to be tested from your textbook. The purpose of the outline format is to speed up and increase your comprehension of the material. Machine learning : a probabilistic perspective offers a comprehensive and self-contained introduction to the field of machine learning, based on a unified, probabilistic approach. The coverage combines breadth and depth, offering necessary background material on such topics as probability, optimization, and linear algebra as well as discussion of recent developments in the field, including conditional random fields, L1 regularization, and deep learning.
Keywords: Machine learning; Probabilities